Risk Factors Associated with Overweight and Obesity Among Females of Reproductive Age Residing in Damak Municipality - Pradhan, Samiksha; Jaisani, Pallavi Vyas (Himalayan Journal of Science and Technology, 2023)
The study was intended to assess risk factors associated with overweight and obesity among females residing in Damak municipality. A cross-sectional quantitative study was performed on 202 females of reproductive age (15–49 years) with a structured questionnaire. Measurements like weight, height, and waist and hip circumference were used to determine indicators of overweight and obesity. General obesity was analyzed using the WHO BMI classification, while Waist Circumference (WC) and Waist to Hip Ratio (WHR) analyzed abdominal obesity based on International Diabetes Federation – IDF, and WHO criteria, respectively. Microsoft Office 16 and SPSS Statistics version 20 were used to analyze data. The Chi-square test was used to establish an association between the variables under study. The study revealed that 31.7% of respondents were overweight, 8.4% were obese, 63.4% were abdominally obese by WC, and 71.8% by WHR. Here, the mean BMI was 25.36±4.56 kg/m2, and the mean WC was 89.69±12.47 cm, with a mean WHR of 0.91±0.09. Age, marital status, family size, parity, sleeping hours, eating pattern, protein intake, and consumption of dairy, eggs, and whole cereals were significantly associated (p<0.05) with overweight and obesity; while age, marital status, education, occupation, family size, parity, and contraceptive use were common factors associated with abdominal obesity (WC and WHR). However, family history, protein intake, and consumption of wheat and eggs were associated (p<0.05) only with WC. The study showed a high prevalence of increased weight among reproductive-aged females in Damak. Thus, being overweight or obese should be viewed as a critical issue. The population should be made aware of the risk factors of obesity.